Recessive MYH6 Mutations in Hypoplastic Left Heart With Reduced Ejection Fraction. (August 2015) - Theis, Jeanne L.; Zimmermann, Michael T.; Evans, Jared M.; Eckloff, Bruce W.; Wieben, Eric D.; Qureshi, Muhammad Y.; O'Leary, Patrick W.; Olson, Timothy M.
<x xml:space="preserve">Abstract</x> Background— The molecular underpinnings of hypoplastic left heart are poorly understood. Staged surgical palliation has dramatically improved survival, yet eventual failure of the systemic right ventricle necessitates cardiac transplantation in a subset of patients. We sought to identify genetic determinants of hypoplastic left heart with latent right ventricular dysfunction in individuals with a Fontan circulation. Methods and Results— Evaluation of cardiac structure and function by echocardiography in patients with hypoplastic left heart and their first-degree relatives identified 5 individuals with right ventricular ejection fraction ⩽40% after Fontan operation. Whole genome sequencing was performed on DNA from 21 family members, filtering for genetic variants with allele frequency <1% predicted to alter protein structure or expression. Secondary family-based filtering for de novo and recessive variants revealed rare inherited missense mutations on both paternal and maternal alleles of MYH6, encoding myosin heavy chain 6, in 2 patients who developed right ventricular dysfunction 3 to 11 years postoperatively. Parents and siblings who were heterozygous carriers had normal echocardiograms. Protein modeling of the 4 highly conserved amino acid substitutions, residing in both head and tail domains, predicted perturbation of protein structure and function. Conclusions— In contrast to dominant MYH6 mutations with variable penetrance identified in other congenital heart defects and dilated cardiomyopathy, this study reveals compound heterozygosity for recessive MYH6 mutations in patients with hypoplastic left heart and reduced systemic right ventricular ejection fraction. These findings implicate a shared molecular basis for the developmental arrest and latent myopathy of left and right ventricles, respectively.